Migration and policies in the European Union: Highly skilled mobility, free movement of labour and recognition of diplomas - Peixoto, João (2001)
This article evaluates the relationship between highly skilled mobility (especially by individuals with university-level degrees) and migration policies. Data from the European Union (EU) and Portugal (in particular) provide the empirical basis of the research. EU policies regarding the free circulation of individuals which aim to build the “common market” for economic factors (including labour) are reviewed, as are the more specific recognition of diplomas policies for professional and academic purposes, and recent levels of international mobility in both the EU and Portugal. The article also enumerates the main obstacles that, from a political and legal or social and cultural perspective, explain the low mobility revealed by those figures. Obstacles include the broad denial of citizenship rights; the necessity of assuring a means of sustenance; linguistic and technical exigencies for diploma recognition; the social attributes of work (more explicit in the service sector); and the institutional nature of national skilled labour markets. The main exception to the low mobility rule – movements of cadres in the internal labour markets of transnational corporations – together with flows in other multinational organizations, are also reviewed. In these, migrations are relatively exempt from political constraints and, significantly, avoid the recognition procedures adopted by the EU. In other words, it seems that the entry of highly skilled individuals in a transnational corporation, and not their citizenship in a Europe without frontiers, is what enables them to achieve effective mobility.